Computer‐modeled global census finds thousands of eddies each year. (28th May 2013) - Kumar, Mohi
Abstract : Eddies, the curls and swirls that spin off swift‐moving ocean currents, help disperse energy and nutrients throughout the world's oceans. Floats and other engineered submersibles can help scientists understand the evolution and path of specific eddies. But knowledge of how many eddies exist, as well as how pervasive, how strong, and how large these eddies are at any given moment, would require continuous and detailed monitoring of the entire ocean at all depths—an impossible feat.